Effect of sodium thiosulfate on some physiological aspects in male rats exposed to silver nitrate - SUHA A. RASHEED (International Journal of Pharma and Bio Sciences, 2019)
The majority of diseases or syndromes are consequences of Reactive Oxygen Species (ROS)-induced oxidative damage. Silver nitrate (SN) is a widely used compound in many fields such as animal treatment and industry, which makes it an intensive pollutant for air and soil. This results in a continuous exposure of both human and animals to SN. Sodium thiosulfate (STS) is a novel antioxidant, previously used as poisons antidote. STS contains thiol (-SH) group, which has antioxidant properties. In this study, the effect of another reactive species called Reactive Nitrogen Species (RNS), yielded by SN administration, were examined for their effects to trigger cellular damage. In addition, we introduced STS, to be used as a treatment for SN-induced damage in male rats. Eighteen adult male rats were randomly divided into three groups, 1) control group, 2) SN group, administered SN (30 mg/kg/day) and 3) SN+STS group, administered SN in addition to STS (400 mg/kg/day). All groups were treated for four weeks then, blood samples and genitalia were obtained from animals of all groups. Blood profile, oxidation markers and fertility indices were assessed for the treated groups against the control. Data analysis revealed that SN administration negatively affected the antioxidant status by elevating serum malondialdehyde (MDA) and reducing glutathione (GSH). Furthermore, RNS adversely affected the male fertility indices including, weight of testicles, total sperm number and ratio of viable sperms. STS efficiently improved the above parameters, amending the oxidant-antioxidant imbalance induced by SN. In conclusion, RNS are active damaging particles for biomolecules however, their effect can be reversed by treatment with STS, suggesting this compound as a promising antioxidant, which can be utilised to treat different illnesses.